MENUJU PEMBANGUNAN HUKUM YANG TRANSENDENTAL - Muhyidin Muhyidin (Journal of Law, Society, and Islamic Civilization, 2019)
Secularization of the norms of life is already a social reality, including the law in it. The belief in the emergence of globalization and global transformation as if new religions apart from the criticism of them is included in every realm of human life. Therefore legal development will not be valid if it does not try to link it to the process of globalization and global transformation. While the time of religion is considered by some (law) circles unable to provide answers to the development of society in this century.The development of transcendental law is an antithesis of secular development, which tries to offer a legal concept by not denying the existence of God in this life.Keywords : Globalization & Global Transformation, Transendental.